2007
DOI: 10.1080/00365510701297464
|View full text |Cite
|
Sign up to set email alerts
|

External quality assessment in the measurement of haemoglobin by blood gas analysers in Belgium

Abstract: For the BGAs from Bayer, Radiometer and Roche, interlaboratory variation ranged from 0.6 % to 4.1 %, indicating good precision and close agreement between centres. A significant negative bias observed on the GEM Premier 3000 using the EDTA anticoagulated blood samples did not appear to be present in fresh heparinized whole blood samples. There was no significant difference in imprecision and bias between Hb measurements on BGA situated in and outside the central laboratory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Several studies have shown that participation in an EQAS for POCT analyses is useful to improve analytical quality; e.g., for mononucleosis tests and urine dip-slide tests in Norway (8,9), for group A streptococcus tests in Finland (10) and in Switzerland (11), for hemoglobin tests in Belgium (12) and for blood glucose tests in Germany (13). The United Kingdom National External Quality Assessment Service (UKNEQAS) has reported their experience with EQAS for POCT INR over a 6-year period, and stated that this kind of control is both possible and necessary for health care professionals to obtain good analytical quality (14).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that participation in an EQAS for POCT analyses is useful to improve analytical quality; e.g., for mononucleosis tests and urine dip-slide tests in Norway (8,9), for group A streptococcus tests in Finland (10) and in Switzerland (11), for hemoglobin tests in Belgium (12) and for blood glucose tests in Germany (13). The United Kingdom National External Quality Assessment Service (UKNEQAS) has reported their experience with EQAS for POCT INR over a 6-year period, and stated that this kind of control is both possible and necessary for health care professionals to obtain good analytical quality (14).…”
Section: Introductionmentioning
confidence: 99%
“…Se observa una ligera correlación positiva significativa (r¼ 0,440; po0,001), indicando que el Cobas s b 221 tiende a sobrestimar la Hb a medida que esta aumenta su valor. Van Blerk et al 16 Figura 3 A, C, E) Análisis de regresión y correlación de los resultados obtenidos para la hemoglobina, la saturación de oxígeno y la oxihemoglobina entre Cobas s b 221 y ABL800 FLEX. La línea continua indica la recta de regresión y la línea discontinua indica la recta de identidad y ¼x.…”
Section: Resultados Y Discusiónunclassified
“…The first 2 mL of arterial blood withdrawn from the butterfly extension tubing was discarded and a further 2.5 mL was collected in a heparinized syringe (Terumo Europe N/V, Belgium). The sample was analysed immediately without temperature correction, with a laboratory co-oximeter blood gas analyser (Siemens RapidPoint 500; Siemens Healthcare Limited, Denmark), and tHb was determined by multiwavelength spectrophotometry (Van Blerk et al 2007). An automated complete calibration process of the co-oximeter was performed as per the manufacturer's instructions every 8 hours.…”
Section: Methodsmentioning
confidence: 99%